The diagnosability of k-ary n-cubes with missing edges. Issue 1 (2nd January 2020) - Fan, Liqiang; Yuan, Jun
ABSTRACT: The k -ary n -cube is a popular interconnection network for many multiprocessor systems because of its good topological structure. In this paper, we investigated the relationship between the fault diagnosability of k -ary n -cube with missing edges and its minimum degree of vertices. Let G be a k -ary n -cube with missing edges and the minimum degree δ ( G ) = r . Then we show that the diagnosability of G is r for r ≥ 3, n ≥ 2 under the PMC model and BGM model. GRAPHICAL ABSTRACT: